PENGARUH FRAUD PENTAGON DALAM MENDETEKSI RISIKO KECURANGAN PELAPORAN KEUANGAN - Ayu Putu Suari Maladewi; Cokorda Gde Bayu Putra (UNHI Press, 2022)
Purpose this research aimed to determine the effect of the pentagon fraud in detecting the risk of fraudulent financial reporting in case studies of consumergoods industrial sector companies listed on the Indonesian stock exchange in 2018-2020. Fraud pentagon has several factors that influence the occurrence of fraud, Pressure is proxied by (financialstability, financialtarget, externalpressure) Opportunity (natureof industry, ineffective monitoring) Rationalization (Change in auditor), Competence (change of director) and Arrogance (frequent number of CEO). The F-score model is used in this study to see the potencial for fraud in financial reporting. The method used for sample selectioninthis study is purposive sampling, with a total sample of 108 companies for 3 years. Hypothesis testing is done by usingmultiple linearregression using SPSS 21.00. Theresults ofthis study indicate that financial stability, nature of industry, ineffective monitoring, change in auditors and change of directors have no significant effect on fraudulent financial reporting, external pressure and frequent number of CEO have a negative and significant effect on fraudulent financial reporting, while financial targets havea positive effect and significant to fraudulent financial reporting